Postpartum bonding: the role of perinatal depression, anxiety and maternal-fetal bonding during pregnancy - Dubber, Star; Wallwiener, Stephanie (Archives of women's mental health, 2015)
Adverse effects of perinatal depression on the mother-child interaction are well documented; however, the influence of maternal-fetal bonding during pregnancy on postpartum bonding has not been clearly identified. The subject of this study was to investigate prospectively the influence of maternal-fetal bonding and perinatal symptoms of anxiety and depression on postpartum mother-infant bonding. Data from 80 women were analyzed for associations of symptoms of depression and anxiety as well as maternal bonding during pregnancy to maternal bonding in the postpartum period using the Edinburgh Postnatal Depression Scale (EPDS), the State-Trait Anxiety Inventory (STAI), the Pregnancy Related Anxiety Questionnaire (PRAQ-R), the Maternal-Fetal Attachment Scale (MFAS) and the Postpartum Bonding Questionnaire (PBQ-16). Maternal education, MFAS, PRAQ-R, EPDS and STAI-T significantly correlated with the PBQ-16. In the final regression model, MFAS and EPDS postpartum remained significant predictors of postpartum bonding and explained 20.8 % of the variance. The results support the hypothesized negative relationship between maternal-fetal bonding and postpartum maternal bonding impairment as well as the role of postpartum depressive symptoms. Early identification of bonding impairment during pregnancy and postpartum depression in mothers plays an important role for the prevention of potential bonding impairment in the early postpartum period.